Perbandingan Paradiplomasi Multi Sektor Surabaya-Busan dan Medan-Gwangju - Roby Rakhmadi (Jurnal Terekam Jejak, 2023)
This research aims to analyze the comparison of policies carried out between Surabaya-Busan and Medan-Gwangju in various sectors as a form of paradiplomacy. The two cities mentioned above are large cities in Indonesia and are quite active in foreign relations. In this article, it is described how Indonesian subnational governments, especially cities, collaborate with cities in South Korea, especially Busan and Gwangju. These two cities are trying to expand cooperation in various fields with cities in South Korea. These two cities are examples of subnational governments that are active in seizing opportunities for collaboration with other subnational parties in multi-sectors. Researchers use the concept of sub-national and twin cities to analyze the comparison of programs carried out by the city of Surabaya towards Busan and the city of Medan towards Gwangju. The use of these two concepts is carried out to help researchers understand in depth the comparison of paradiplomacy carried out to achieve their respective interests. This research uses a descriptive qualitative method based on books, journals and official websites. Researchers used previous research which was adapted to complete this article.